Magnetic Resonance Imaging of the Bowel: Today and Tomorrow - Kinner, S.; Hahnemann, M. L.; Forsting, M.; Lauenstein, T. C. (RöFo - Fortschritte auf dem Gebiet der Röntgenstrahlen und der bildgebenden Verfahren, 2015)
Magnetic resonance imaging of the small bowel has been feasible for more than 15 years. This review is meant to give an overview of typical techniques, sequences and indications. Furthermore, newly evaluated promising techniques are presented, which have an impact on the advance of MR imaging of the small and large bowel.Key Points:• T2-weighted sequences both with and without fat saturation and T1-weighted fat saturated sequences prior to and following intravenous injection of a gadolinium-based contrast medium contitute the basics for bowel MR imaging.• Newer MR applications, such as diffusion-weighted imaging or contrast-enhaced dynamic sequences supply addtional information; they should thus be integrated in a regular sequence protocol für bowel MRI.• Additional new modalities like motility imaging and PET/MRI have to be evaluated in future studies.Citation Format:• Kinner S, Hahnemann ML, Forsting M et al. Magnetic Resonance Imaging of the Bowel: Today and Tomorrow. Fortschr Röntgenstr 2015; 187: 160 – 167
Keywords: small bowel; MR-imaging; technical aspects; motility; imaging sequences